TO STUDY OF DISTRIBUTION EXTRA-PULMONARY TUBERCULOSIS PATIENTS ACCORDING TO SITES TREATED UNDER RNTCP IN KARAD TUBERCULOSIS UNIT - Bhoi, Anil; Bhoi, Vandana (Journal of evolution of medical and dental sciences, 2015)
BACKGROUND: The Revised National Tuberculosis Programme (RNTCP) in INDIA. OBJECTIVES: To study of distribution of extra-pulmonary tuberculosis patients according to sites treated under RNTCP in Karad Tuberculosis Unit. MATERIAL & METHODS: The present longitudinal study was carried out during January 2008 to June 2009 on patients registered at Karad TU cattering 9 PHCs, Sub District Hospital, Krishna Hospital & 6 DMCs with 3ICTCs. In total 806 patients were study subjects with prior permission of District Tuberculosis Officer (DTO). Patients were interviewed using semi structured questionnaires at their residence in defined time period i.e. at the start of treatment, after completion of IP. RESULTS & OBSERVATIONS: In this study there was higher proportion of males 390(82.1%) having pulmonary tuberculosis than females 230(69.5%) and higher proportion of females 101(30.5%) having extra pulmonary tuberculosis than males 85(17.9%) in this study. There was highly significant association between type of TB and gender. Out of 186 extra pulmonary tuberculosis patients maximum 83(42.8%) had lymphadenopathy while 31(16%) suffered from pleural effusion. 40(21.5%) had abdominal tuberculosis, 13(6.7%) had tuberculosis meningitis. CONCLUSION: The females were having higher proportion 101(30.5%) of extra pulmonary tuberculosis than males 85(17.9%) in this study. The lymph nodes 83(42.8%) was the commonest site for extra pulmonary tuberculosis in this present study. KEYWORDS: RNTCP, TU, PHC, DMC, ICTC, IP, TB, EPTB.